2013
DOI: 10.2166/wh.2013.257
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultraviolet light disinfection on tetracycline-resistant bacteria in wastewater effluents

Abstract: The ubiquitous use of antibiotics has led to an increasing number of antibiotic-resistant bacterial strains, including strains that are multidrug-resistant, pathogenic, or both. There is also evidence to suggest that antibiotic resistance genes (ARGs) spread to the environment, humans, and animals through wastewater effluents. The overall objective of this study was to investigate the effect of ultraviolet (UV) light disinfection on antibiotic-resistant bacteria. Wastewater effluent samples from a wastewater t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…One of the tasks of a WWTP is the disinfection of wastewater. Ultraviolet radiation and chemical agents are most commonly used for these purposes (Aslani et al, 2014 ; Childress et al, 2014 ). Both these procedures are expensive, and the latter, chemical wastewater treatment, may be harmful for the environment.…”
Section: Discussionmentioning
confidence: 99%
“…One of the tasks of a WWTP is the disinfection of wastewater. Ultraviolet radiation and chemical agents are most commonly used for these purposes (Aslani et al, 2014 ; Childress et al, 2014 ). Both these procedures are expensive, and the latter, chemical wastewater treatment, may be harmful for the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Due to an insufficient number of studies related to the removal of ARG and ARB from HWW, studies pertaining to the removal of ARB and ARG from all kinds of water matrices have also been highlighted in this work. Disinfection was found to be very efficient in terms of drastically reducing the number of ARB and ARG in wastewater [120] , [121] , [122] , [123] , [124] , [125] . In order to inactivate the ARG inside the bacteria cells, the disinfectant should be able to pass through the cell envelope without getting bound to other cellular constituents.…”
Section: Pilot/full-scale Treatment Systems For Hww Managementmentioning
confidence: 99%
“…Efficacy of chlorine to inactivate pathogens is impacted by several factors, including chlorine concentration, pH, contact time, and the bacterial pathogen strain; as the response of Gram negative bacteria against chlorine differ from Gram positive bacteria [11]. Many studies have shown that both chlorine and UV disinfection are effective in reducing concentrations of resistant bacteria [12,13]. Another study [14] also suggested that UV treatment followed by chlorine disinfection may provide enhanced reduction of antibiotic resistant bacteria (ARB) in wastewater effluent, albeit at significantly higher doses and contact times than are commonly employed.…”
Section: Introductionmentioning
confidence: 99%
“…The OCland HOCl species are commonly called free chlorine, which are extremely reactive with numerous components of the bacterial cell [12].…”
Section: Introductionmentioning
confidence: 99%